MEMAHAMI PENGARUH BUDAYA ORGANISASI ISLAM DALAM PERUBAHAN ORGANISASI - Nirwan Nazaruddin; Anton Hindardjo (Jurnal Asy-Syukriyyah, 2015)
Organizational culture is growing because it was created and developed by individuals working in an organization, leaders play a very important role in imparting their view of organizational culture. Leaders play an important role in instilling a culture of the organization, being a role model that can be emulated, able to create a system of rules, and be able to build an organizational culture. Leaders should also be able to establish a fair penalty system, showing sensitivity to the customer and are sensitive to opinions. Therefore, building a new culture within the organization requires careful planning. Besides the attitude that should be owned by every activist organization, is that sincerity, solidarity and sacrifice.